FROM MERGER TO DIVESTITURE: FINANCIAL PERFORMANCE, ECONOMIC VALUE ADDED, AND MARKET REACTION TO GOTO’S SALE OF TOKOPEDIA TO BYTEDANCE - Dhea Rakhmatika Utami; Yunieta Anny Nainggolan; Subiakto Soekarno (RADJA PUBLIKA, 2025)
This studies examines how PT GoTo Gojek Tokopedia Tbk (GoTo) is affected by its decision to divest most of its shares in Tokopedia to ByteDance (TikTok), while keeping a minority stake and forming a commercial partnership. Before this step, GoTo tried to build a “super-app” that combined Gojek’s on-demand services, Tokopedia’s e-commerce, and GoPay. However, even after the merger and IPO, GoTo still recorded large losses, high cash burn, and a declining share price, so it is important to test whether the divestiture really supports long-term value creation. The research uses a single-case, explanatory design covering 2022–2024. It relies only on secondary data: audited financial statements, annual reports, daily stock prices of GoTo. JK and the Jakarta Composite Index (IHSG), press releases, and news. The analysis has three parts: (i) financial ratio analysis (revenue growth, operating margin, EBITDA, net profit margin, ROA, ROE); (ii) Economic Value Added (EVA), using NOPAT, invested capital, and a WACC estimated with CAPM; and (iii) an event study with a market-adjusted model to measure abnormal returns and cumulative abnormal returns (CAR) around the announcement of the Tokopedia–TikTok transaction. The results show that GoTo’s operating performance improves after the divestiture: operating margins become less negative, EBITDA turns positive in 2024, and net loss decreases, although EVA remains negative, even if the value destruction becomes smaller over time. The event study finds short-term positive abnormal returns around the announcement, indicating that investors initially welcome the deal, even though share-price volatility shows remaining concerns. Overall, the thesis concludes that the divestiture makes GoTo smaller, more focused, and more disciplined, but it has not yet fully solved the problem of negative EVA.